A articulação na obra Charanga Jazz Mambo a partir da influência da música afro-cubana - Milet, Roberto Wagner (2013)
The present work is a study on the relationship in music for brass quintet and percussion Charanga Jazz Mambo by Pedro Rodrigues Carneiro, focusing on expressive accents, specifically in the diction used by brass players. Based on the analogy developed by Harnoncourt (1998) between the onset of sound and speech, as well as, the historical changes of attitude in relation to composers writing detailed the score, the research points to the development of instrumental technique, exposing the model standard quintet metals, their variations as well as collaboration in the drafting, interpretation and dissemination of the piece contained in this work. As a source of information about the author, still unknown in academia, we present a brief biography of the composer. Expressive elements such as tempo and articulation, are explained in the description of the work, focusing attention on expressive accents, suggesting the phonemes “TA” or “DA” depending on the nature harder or softer, respectively, from the beginning of each note.